PELATIHAN ZOOM CLOUD MEETING DAN STREAMING YOUTUBE UNTUK PEMBERDAYAAN KOMUNITAS MAJELIS TAKLIM ONLINE - Nada Arina Romli; Dini Safitri; Suci Nurpratiwi; Jessica Lea Alexander (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The current pandemic period has resulted in many restrictions on all offline activities. Online activities are required, one of which is online recitation activities at the Al-Hijrah Ta'lim Council, Pulo Gebang, Cakung. However, the use of online media has not been understood by all participants of the Al-Hijrah Ta'lim Council. Many members of the taklim assembly do not know about zoom and the use of zoom for seminars, conferences, or online studies. The pre-test results showed that 50% of the participants did not know about the zoom platform and the use of zoom for online studies. So there is a need for training for Majellis Ta'lim participants in optimizing the use of Zoom Meetings and Youtube Streaming so that the online recitation process can be carried out correctly.  In meetings and training, service zoom youtube streaming for taklim online community empowerment has been attended by 20 participants. The activity went well, and the communication created was two-way due to the active participation of participants who asked questions. The training results showed an increase in the knowledge of the participants from the survey results that as many as 80% of the participants knew how to use zoom for online study meetings.